Evaluation of psoriasis patients with long-term topical corticosteroids for their risk of developing adrenal insufficiency, Cushing's syndrome and osteoporosis - Betul Erdem; Muzeyyen Gonul; Ilknur Ozturk Unsal; Seyda Ozdemir Sahingoz (Taylor & Francis Group, 2024)
AbstractPurpose In this study, we will investigate the possible side effects of psoriasis patients using long-term topical corticosteroids (TCS) such as adrenal insufficiency, Cushing's Syndrome (CS) and osteoporosis and determine how these side effects develop.Material and Methods Forty-nine patients were included in the study. The patients were divided into two groups based on the potency of the topical steroid they took and the patients' ACTH, cortisol and bone densitometer values were evaluated.Results There was no significant difference between the two groups regarding the development of surrenal insufficiency, CS and osteoporosis. One patient in group 1 and 4 patients in group 2 were evaluated as iatrogenic CS. ACTH stimulation tests of these patients in group 2 showed consistent results with adrenal insufficiency, while no adrenal insufficiency was detected in the patient in Group 1. Patients who used more than 50g of superpotent topical steroids per week compared to patients who used 50g of superpotent topical steroids per week. It was identified that patients who used more than 50g of superpotent topical steroids had significantly lower cortisol levels, with a negatively significant correlation between cortisol level and the amount of topical steroid use (p < .01).Osteoporosis was detected in 3 patients in group 1 and 8 patients in Group 2. Because of the low number of patients between two groups, statistical analysis could not be performed to determine the risk factors.Conclusions Our study is the first study that we know of that investigated these three side effects. We have shown that the development of CS, adrenal insufficiency and osteoporosis in patients who use topical steroids for a long time depends on the weekly TCS dosage and the risk increases when it exceeds the threshold of 50 grams per week. therefore, our recommendation would be to avoid long-term use of superpotent steroids and to choose from the medium-potent group if it is to be used.